Effectiveness of intrathecal nicardipine on cerebral vasospasm in non-traumatic subarachnoid hemorrhage: a systematic review protocol. (March 2017) - Stuart, Daniel; Christian, Robin; Uschmann, Hartmut
Abstract : Review question/objective: The objective of this review is to determine the effectiveness of intrathecal (IT) nicardipine on cerebral vasospasm and its impact on the following outcome measures: mean flow velocities, angiographic and/or clinical vasospasm and infection rates. Specifically, the review question is: What is the effectiveness of IT nicardipine on cerebral vasospasm in adult patients with aneurysmal subarachnoid hemorrhage?